ANALISIS KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN - Conie Nopinda Br Sitepu; Menanti Sembiring (Universitas Quality, 2022)
The purpose of this study was to determine and analyze the effect of product quality on customer satisfaction of UD Pak Suroto's soy milk. This type of research is descriptive with a quantitative approach. The method of determining the sample using the slovin formula totaling 100 people. The data analysis technique used is validity test, reliability test, normality test, heteroscedasticity test, partial test (t test) and coefficient of determination test (R2). The method used is a simple linear regression method. The results showed that product quality partially had a positive effect on customer satisfaction where the tcount value was greater than the ttable value, namely 5.356>1.660 with a significance level of 0.000 <0.05. The result of the determination coefficient test (R²) is 0.226 which indicates that product quality can explain the customer satisfaction variable by 22.6%, the remaining 74.4% is explained by other variables not proposed in this study.